PENGARUH PENGEMBANGAN KARIR DAN MOTIVASI PEGAWAI TEHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI MEDIASI (Studi Pegawai di Sekretariat Daerah Kabupaten Kendal) - Kuat Sugiyanto, 11.52.02.0027 (Students Journal of Economic and Management, 2013)
This study aims to examine and analyze effect of career development and motivation on job satisfaction and the influence of career development, motivation and job satisfaction on employee performance.. What research is at Kendal Regional Secretariat, the study sample totaled 101 respondents, using purposive sampling method, with a minimum of high school education criteria and years> 5 years. Measurements using a Likert scale of 7 (seven) alternative answers. The results of the regression analysis for the first model produced coefficient of determination equal to 0679, which means that the ability of the independent variables in explaining the variation in the dependent variable (the variable job satisfaction) of 67.9%, the remaining 32.1% is explained by other variables outside the model. As for the second model in the coefficient of determination equal to 0530, which means that the ability of the independent variables in explaining the variation in the dependent variable (the variable performance of employees) by 53%, the remaining 47% is explained by other variables outside the model. This study demonstrates (1) career development and employee motivation positive effect on job satisfaction, (2) career development has positive effect on employee performance, (3) job satisfaction has positive effect on employee performance, while (4) does not affect employee motivation employee performance . The results also showed that career development, employee motivation and job satisfaction are jointly positive effect. Key words :Â Career Development, Employee Motivation, Job Satisfaction, and Employee Performance.